The relationship self-efficacy and some of demographic characteristics with leisure time physical activities of Iranian workers - Mahdieh Irom; Ali Zareı; Farshad Tojarı (Türk Spor ve Egzersiz Dergisi)
In this research what we aim to study as LTPA , means activities such as exercise, sport, leisure activities or hobbies which are not related to regular activities job duties, housework and daily commuting , were examined within a week. This study is a survey with sample population of 384 workers from 15 provinces, including 102 females and 282 males who were classified in five age categories, assessing their health status, 30.4 percent of them in fair health, respectively. Data collection were conducted through a demographic questionnaire, participation in leisure-time physical activity and self-efficacy. In order to describe the data, descriptive statistics, chi-square test, Phi correlation and Univariate and multivariate regression analysis was applied (P lt;0.05). The findings of the study shows that there is a significant and meaningful association between age, gender, leisure time physical activity. Also gender was significantly associated with self-efficacy but age were not significant .The relationship between self-efficacy and external barriers with leisure time physical activity were significant but there was not significant relationship between internal barriers of self-efficacy and leisure time physical activity .The results showed that the less participating of woman in leisure-time physical activity Despite its benefits in increasing health awareness, suggest their undesirable lifestyle in this area. Obviously, continuation of programs Sports, promoting exercise and practicing it in the workplace can be an effective step towards achieving the abovementioned goals.